Economics of Land Degradation and Improvement – A Global Assessment for Sustainable Development 2015
DOI: 10.1007/978-3-319-19168-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Land Degradation in Sub-Saharan Africa

Abstract: Sub-Saharan Africa (SSA) has experienced the most severe land degradation in the world. Given that livelihoods of the majority of the rural poor heavily depend on natural resources, countries in the region have designed a number of policies and strategies to address land degradation and to enhance productivity. However investment from both countries and their development partners has remained low, especially for livestock, which accounts for the largest area degraded. Our results show that conversion of grassl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 67 publications
0
58
0
1
Order By: Relevance
“…Although the drivers of land degradation vary from region to region, major causes across different regions include the conversion of (i) forests to grazing lands, (ii) grassland to barren land and shrublands, and (iii) grassland to cropland (Eswaran et al 2001;UNCCD 2013;Nkonya et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although the drivers of land degradation vary from region to region, major causes across different regions include the conversion of (i) forests to grazing lands, (ii) grassland to barren land and shrublands, and (iii) grassland to cropland (Eswaran et al 2001;UNCCD 2013;Nkonya et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A typical farm household would be adopting one or more of the components of ISFM if and only if the expected benefit is higher than otherwise. Although the ISFM components are framed on the assumption that synergistic results can be obtained when complementary technologies are co‐implemented (Nkonya et al, ), there is also an array of similar technologies within the subset of components that can be substituted (Lambrecht et al, ). The equation for multivariate probit model is structured following Kassie et al .…”
Section: Methodsmentioning
confidence: 99%
“…It is projected that by the year 2050, ISFM technologies could increase maize yields in the Sub‐Saharan Africa (SSA) region by 21.5% (Rosegrant et al, ). From an economic standpoint, studies have also revealed that the cost of implementing ISFM technologies is lower than the opportunity costs associated with not investing resources in soil fertility management (Nkonya et al, ). In their study, based on data from seven countries in Sub‐Saharan Africa, Nkonya et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations